2003
DOI: 10.5860/crl.64.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Instruction for Web Searching: An Empirical Study

Abstract: Users searching the Web have difficulty using search engines and developing queries. Searches tend to be simple, and Boolean operators are used infrequently and incorrectly. Users also are unaware that search engines operate differently from other information retrieval systems. Yet, there is little research on effective instructional methods for teaching users how to search the Web. Research has looked at instructional methods for other types of information retrieval, but these systems differ a great deal from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…While previous interventions have attempted to develop subskills in the process of IPS (e.g. Britt & Aglinskas, 2002;Colaric, 2003;Walraven, Brand-Gruwel, & Boshuizen, 2013), this experiment attempted to provide a systematic approach to the whole task of solving an information problem following the 4C/ID whole task approach . This intervention was successful, as shown by the significant increase in scores between pretest and posttest.…”
Section: Discussionmentioning
confidence: 99%
“…While previous interventions have attempted to develop subskills in the process of IPS (e.g. Britt & Aglinskas, 2002;Colaric, 2003;Walraven, Brand-Gruwel, & Boshuizen, 2013), this experiment attempted to provide a systematic approach to the whole task of solving an information problem following the 4C/ID whole task approach . This intervention was successful, as shown by the significant increase in scores between pretest and posttest.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the queries showed that 38% of the search terms came from the search statement, and 23% of the search terms were added by users during the interaction with the intermediaries, which means that 62% of the search terms were contributed by the user. Colaric () concluded in her experiment that 87% of the participants relied exclusively on the terms from the task phrasing. Hsieh‐Yee () compared the behavior of novice and expert searchers researching familiar and unfamiliar subjects in the ERIC database on the DIALOG system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, there is little research on effective web-searching instruction. Colaric (2003) examined three instructional treatments to aid searchers in developing queries (ie, planning). The results were equivocal.…”
Section: Introductionmentioning
confidence: 99%